Trace metal pyritization variability in response to mangrove soil aerobic and anaerobic oxidation processes - Machado, W. (2014)
The degree of iron pyritization (DOP) and degree of trace metal pyritization (DTMP) were evaluated in mangrove soil profiles from an estuarine area located in Rio de Janeiro (SE Brazil). The soil pH was negatively correlated with redox potential (Eh) and positively correlated with DOP and DTMP of some elements (Mn, Cu and Pb), suggesting that pyrite oxidation generated acidity and can affect the importance of pyrite as a trace metal-binding phase, mainly in response to spatial variability in tidal flooding. Besides these aerobic oxidation effects, results from a sequential extraction analyses of reactive phases evidenced that Mn oxidized phase consumption in reaction with pyrite can be also important to determine the pyritization of trace elements. Cumulative effects of these aerobic and anaerobic oxidation processes were evidenced as factors affecting the capacity of mangrove soils to act as a sink for trace metals through pyritization processes.